Osteoarthritis Progression: Mitigation and Rehabilitation Strategies - Drummer, Devin; McAdam, Jeremy; Seay, Regina; Ferrando, Arny; Bridges, S. Louis; Singh, Jasvinder A.; Bamman, Marcas (Frontiers in Rehabilitation Sciences, 2021)
Osteoarthritis is the most common form of arthritis and is a substantial burden for patients with the disease. Currently, there is no cure for osteoarthritis, but many emerging therapies have been developed to aid in the mitigation of disease progression. When osteoarthritis reaches the end-stage of disease many patients undergo total joint arthroplasty to improve quality of life, yet some experience persistent pain and mobility limitations for extended periods following surgery. This review highlights recent therapeutic advancements in osteoarthritis treatment consisting of pharmacologics, nutraceuticals, biologics, and exercise while emphasizing the current state of post-arthroplasty rehabilitation.